Challenges for adherence to bacterial resistance actions in large hospitals - Mariana Sanches de Mello; Adriana Cristina Oliveira (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to identify the challenges to actions to contain bacterial resistance. Methods: cross-sectional study, carried out in 30 large-sized hospitals in Minas Gerais, from 2018 to 2019. The professionals were interviewed, and the environment and actions to prevent bacterial resistance were observed. Results: regarding the knowledge of health care professionals about the measures of bacterial resistance prevention, 78.3% did not correctly describe the five moments of hand hygiene, and 76.6% did not correctly describe the measures to control bacterial resistance. The simple hygiene of hands, followed by alcohol rubbing was predominant (48.3%) among workers, and soap dispensers were next to alcohol dispensers in 58.3% of the nursing stations in care units. Conclusions: the insufficient knowledge from the professionals, which is a failure related to the physical structure and to personal protection equipment, are factors that difficult the adherence to measures to contain bacterial resistance in hospitals.